2012
DOI: 10.1016/j.jconrel.2011.09.074
|View full text |Cite
|
Sign up to set email alerts
|

Addition of ascorbic acid to the extracellular environment activates lipoplexes of a ferrocenyl lipid and promotes cell transfection

Abstract: The level of cell transfection mediated by lipoplexes formed using the ferrocenyl lipid bis(11-ferrocenylundecyl)dimethylammonium bromide (BFDMA) depends strongly on the oxidation state of the two ferrocenyl groups of the lipid (reduced BFDMA generally mediates high levels of transfection, but oxidized BFDMA mediates very low levels of transfection). Here, we report that it is possible to chemically transform inactive lipoplexes (formed using oxidized BFMDA) to “active” lipoplexes that mediate high levels of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
66
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(74 citation statements)
references
References 57 publications
8
66
0
Order By: Relevance
“…We used serum-free media for all of the cell-based studies reported here to permit comparison to the results of past studies on BFDMA/DNA lipoplexes and to facilitate biophysical characterization. 2931,33,35,36 …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We used serum-free media for all of the cell-based studies reported here to permit comparison to the results of past studies on BFDMA/DNA lipoplexes and to facilitate biophysical characterization. 2931,33,35,36 …”
Section: Resultsmentioning
confidence: 99%
“…We demonstrated in past studies that the addition of small-molecule chemical reducing agents (such as glutathione 31 or ascorbic acid, AA 33 ) to lipoplexes of oxidized BFDMA and plasmid DNA can be used to activate these otherwise “inactive” lipoplexes and promote higher levels of cell transfection. Additional results shown in Figure 2 (white bars) demonstrate that this approach can also be used as a practical means to activate lipoplexes of oxidized BFDMA and siRNA.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Dodecyltrimethylammonium bromide DTAB was added to the dilute solutions to eliminate cloudy solutions of 11-FAB 29,30 . DTAB does not absorb visible light wavelength 400-700 nm .…”
Section: Uv-vis Measurementsmentioning
confidence: 99%